Abundance and Characteristics of Coliform Bacteria in Bakasang Sia-sia (Sipunculus nodus L) - Mahulette, Ferymon; Lesbassa, Chelsia Venjelin; Pattipeilohy, Mery (LenteraBio : Berkala Ilmiah Biologi, 2024)
Bakasang sia-sia is a fermented product made from peanut worms (Sipunculus nodus) which is processed by the people of the Tanimbar Islands, Maluku. Uncontrolled processing allows the presence of coliform bacteria in this local food product. Preservatives added in the processing of bakasang sia-sia are very diverse. This study aimed to isolate and characterize coliform bacteria from bakasang sia-sia which is processed using different preservatives. Coliform bacteria were enumerated and isolated using Lactose broth (LB) and Eosin methylene blue agar (EMBA) media respectively, then characterized macroscopically and microscopically. Determination of the number of coliform bacteria using the Most probable number (MPN) method in a series of 3 tubes. The results showed that the number of coliform bacteria in bakasang sia-sia processed using salt and citrus liquid was 210 MPN/g, higher than bakasang sia-sia using borassus vinegar which only reached 28 MPN/g. It is suspected that the coliform bacteria found in bakasang sia-sia belong to the genera Escherichia, Enterobacter, and Citrobacter. Bakasang sia-sia needs to be optimized for processing in a controlled fermentation to improve the quality of this local food product in the future.